AI Conversational Agents for Corporate Language Learning: Enhancing Engagement and Retention - Salvetti, Fernando; Bertagni, Barbara; Contardo, Ianna (International Journal of Advanced Corporate Learning (iJAC), 2025)
e-REAL Labs are at the forefront of language education innovation, integrating AI-driven conversational agents (avatars) to transform the learning experience. These avatars serve as interactive partners in a cooperative learning framework, engaging students in dynamic, real-life dialogues tailored to their proficiency levels. By fostering an inclusive and adaptive environment, they encourage active participation and facilitate group-based language activities, enhancing collaboration and communication. The AI avatars are pivotal in guiding learners through interactive problem-solving tasks, compelling them to negotiate meaning, resolve misunderstandings, and build linguistic competence through adaptive feedback. This immersive approach accelerates language acquisition and cultivates essential social skills such as cultural awareness, critical thinking, and teamwork. Through scenario-based interactions that demand cooperation, e-REAL Labs’ AI-powered methodology ensures that every learner contributes to group success, creating a rich and engaging language-learning experience.